Crimes against nature environmental criminology and ecological justice - White, R. D. (Robert Douglas) 1956- (Gale virtual reference library, 2008)
Provides an account and analysis of the key concerns of green criminology. Provides numerous examples of crimes against the environment - ranging from toxic waste, logging, wildlife smuggling, bio-piracy, the use and transport of ozone depleting substances through to illegal logging and fishing, water pollution and animal abuse.